PENGARUH FINTECH DAN ECCOMERCE TERHADAP KINERJA KEUANGAN UMKM DI INDONESIA - Hambali, HM Ridlwan; Nendissa, Sandriana J; Mayndarto, Eko Cahyo; Djibran, Moh. Muchlis; Dinsar, Arfandy (ITB AAS Indonesia Surakarta, 2024)
This research explains the impact of the use of financial technology (Fintech) and electronic commerce (E-commerce) on the financial performance of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Along with the rapid development of information and communication technology, especially in the Fintech and E-commerce sectors, MSMEs are becoming the center of attention as strategic elements of the national economy. The aim of this research is to identify the positive or negative influence of Fintech and E-commerce on the financial performance of MSMEs. Data analysis methods include multiple linear regression, partial T test, and simultaneous F test. The research results show that Fintech and E-commerce have a positive and significant impact on the financial performance of MSMEs. Regression analysis highlights a significant relationship between both independent variables and financial performance, with positive regression coefficients for Fintech and E-commerce. Partial T tests confirmed that each variable exerted a significant effect individually, while simultaneous F tests showed significant joint effects. The findings of this research provide practical implications in improving performance strategies, supporting informational managerial decisions, formulating business policies, and emphasizing the importance of influencing factors, namely Fintech and E-commerce. In conclusion, the use of Fintech and E-commerce can be considered an effective strategy for improving the financial performance of MSMEs in Indonesia. These implications provide a basis for decision making and improving strategies in facing the challenges and opportunities of the MSME sector in the digital era.